Kualitas pembelajaran matematika MTs di masa pandemi Covid-19 - Erpin Evendi, Erpin Evendi; Sayid Wahyu Alwi Sidik Al idrus, Sayid Wahyu Alwi Sidik Al idrus; Patma Halmayda, Patma Halmayda (Jurnal of Math Tadris, 2021)
The implementation of mathematics learning in the COVID-19 period must be tested for quality, one of which is by knowing the quality of evaluation tests used during online learning in schools.The purpose of this study is to find out the quality of MTs math learning ecvaluation tests during the COVID-19 Pandemic through analysis of the quality of evaluation tests used. A good test should meet standards in validity, reliability, differentiating power, appropriate level of difficulty. The research method used is a quantitative descriptive research method conducted at MTs NW Nadhatul Abror NW Nyangget Mataram through three stages of activities, namely preparation, implementation and completion. Quantitative data obtained is a score of mathematical problem-solving skills. Data analysis techniques are used quantitatively to determine the level of quality of instruments empirically while qualitative to determine the category of validity, reliability, different power and difficulty level of test instruments. The results showed that there were 13 questions of good quality, 10 revised and 17 rejected with an average difficulty level of question items = 0.685 and had been able to distinguish students in high and low grades. The 13 issues are included in the problem with high validity and good reliability.